2013
DOI: 10.4161/psb.24354
|View full text |Cite
|
Sign up to set email alerts
|

High frequency regeneration via direct somatic embryogenesis and efficientAgrobacterium- mediated genetic transformation of tobacco

Abstract: A direct somatic embryogenesis protocol was developed for four cultivars of Nicotiana species, by using leaf disc as an explant. Direct somatic embryogenesis of Nicotiana by using BAP and IAA has not been investigated so far. This method does not require formation of callus tissues which leads to somaclonal variations. The frequency of somatic embryogenesis was strongly influenced by the plant growth hormones. The somatic embryos developing directly from explant tissue were noticed after 6 d of culture. Somati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…Interestingly, it is well known that the two species show different regeneration behaviors in vitro; the explants from the former easily develop adventitious shoots in response to cytokinin, but rarely show somatic embryogenesis, whereas those from the latter easily develop embryogenic calluses in response to auxin, but rarely develop adventitious shoots. There are some reports regarding somatic embryogenesis in tobacco tissue culture (Gill and Saxena 1993;Guo et al 2013;Pathi et al 2013;Srinivasan et al 2007); however, the researchers may have observed organogenesis but not embryogenesis, judging from their use of shoot inducers (cytokinin) in the culture and morphological aspect and greenish color shown in the figures in their reports. Previously, in tobacco tissue and cell culture, cytokinin was essential for regeneration with the exception of pollen embryogenesis (Kyo et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it is well known that the two species show different regeneration behaviors in vitro; the explants from the former easily develop adventitious shoots in response to cytokinin, but rarely show somatic embryogenesis, whereas those from the latter easily develop embryogenic calluses in response to auxin, but rarely develop adventitious shoots. There are some reports regarding somatic embryogenesis in tobacco tissue culture (Gill and Saxena 1993;Guo et al 2013;Pathi et al 2013;Srinivasan et al 2007); however, the researchers may have observed organogenesis but not embryogenesis, judging from their use of shoot inducers (cytokinin) in the culture and morphological aspect and greenish color shown in the figures in their reports. Previously, in tobacco tissue and cell culture, cytokinin was essential for regeneration with the exception of pollen embryogenesis (Kyo et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…They also allow large-scale production of synthetic plants and seeds, which have the advantages of ease of handling and transport, long-term storage potential, uniform production, and the potential for automating the entire production process (Pathi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The bipolarity linked to the single cell origin of the embryos may reduce the development of chimeras or mixoploidy in the regenerants (Pathi et al 2013). Somatic embryogenesis may occur directly or in an indirect way.…”
Section: Somatic Embryogenesis As a Key Morphogenic Pathway For Genetmentioning
confidence: 99%